Qualidade da luz no crescimento in vitro e aclimatação de dois cultivares de Phalaenopsis amabilis Blume (Orchidaceae) - Massaro, Raquel (2013)
Orchidaceae is one of the largest and diverse families of angiosperms, that is in almost every type of habitat, except tundras and deserts. They are considered of great ornamental importance, the genus Phalaenopsis has received a great prominence having increaed and its production enlarged in the Gross and inner market This way, the Brazilian floriculture market has a great demand in seedling production, requiring more studies and researches involving biotechnologycal techniques from the development of vases and containers on a prepared substrate, propagation techniques and acclimatization. And with in vitro culture, it is possible that the desirable plant coul be multiplied through several sucbultures, which enables an earlier and new cultivation available more quickly for commercial use. The luminosity is another factor that is gaining prominence in the productivity of orchids, the fact that the quality of light affects directly the growth and development of plants grown in vitro and/or ex vitro. The present work had as objective to anlyze the growth of in vitro and acclimatization in the two cultivations (cv. 6323 and cv. 6546) of orchid Phalaenopsis amabilis Blume, under different lighting spectra. Inicially it occurred the sowing the seedling in the cultivation enviroment MS that were enveloped with different cellophanes: yellow, blue, Green, red, and white. After 60 cultivation days it was performed an statistical evaluation on the seedling. Afterward, they were put in collective vases to the phase of acclimatization, and those ones stand for more three months. Through analyze the biometric data it can be observed that the growing in vitro and ex vitro of Phalaenopsis amabilis was influenced by many different spectra lights, considering that the various results of this influence from the genotype. It can be observed that the blue spectrum performed a great performance on cv. 6323 and on the Green spectrum cv. 6546.